Analysis of the Dynamic Characteristics of the Distillation Column of Plate Type - E. S. Gebel (EAI Endorsed Transactions on Energy Web, 2017)
The relevance of the study related to the necessity to convert to “unmanned” production in a refinery and, as a consequence, we must derive a mathematical model of the high-octane gasoline process. This paper introduces a calculation procedure for modelling and dynamic analysis of a condensate distillation (rectification) column using by the mass balance structure. In this study, the reflux rate and the boil up rate are used as the inputs of the purity of the distillate overhead and the impurity of the bottom products. The dynamic analysis is accomplished over two phases: the basis nonlinear model of the plant and the full-order linearized model. This information will be used for modelling simulation to verify the applicable ability of the dynamic model and then to analyse and synthesize of the predictive model of the automatic control system of the rectification column.